Oriental cultures represented in the opera “Samson et Dalila” by Camille Saint-Saens - Karácsony, Noémi (Bulletin of the Transilvania University of Brasov. Series VIII: Performing Arts. Vol. 11(60) No. 1 (2018), 2018)
The present paper focuses on the manner in which foreign cultures belonging to the Oriental world are represented in the opera “Samson et Dalila” composed by Camille Saint-Saëns. Orientalist art strives for the representation of the exotic and unknown, but at the same time, it may point to those aspects of the “self” that need to be changed. In Saint-Saëns’ opera two Oriental, but altogether different cultures are portrayed, the Hebrews and the Philistines, the contrast between which could as well mirror the differences between East and West. Yet, the representation of the Orient is achieved mainly through the use of traditional Western componistic techniques, and alterity is suggested in a very subtle manner, often through stereotypes. With “Samson et Dalila” Camille Saint-Saëns created an opera that anticipates the path of his successors, the harmonious union between music and dramatic action offering numerous possibilities of interpretation.
Keywords: Orient; West; Hebrews; Philistines; contrast